(untitled) (Swiss Medical Weekly, 2013)
INTRODUCTION: Infertility treatments are a major source of the increase in multiple pregnancies (MPs). AIMS: The aims of the present study were (1.) to investigate the origin and maternal/neonatal outcomes of MP and (2.) to review the different measures that can be adopted to reduce these serious complications. METHODS: The study included all women with multiple births between 1 January 1995 and 31 December 2006 at the University Hospital of Bern, Switzerland. The outcomes associated with the various origins of MP (natural conception, ovarian stimulation [OS] ‒ in-vitro fertilisation [IVF-ICSI]) were analysed using a multinomial logistic regression model. An analysis of the Swiss law on reproductive medicine and its current proposed revision, as well as a literature review using Pubmed, was carried out. RESULTS: A total of 592 MP were registered, 91% (n = 537) resulted in live births. There was significantly more neonatal/maternal morbidity in MP after OS compared with natural conception and even with the IVF-ICSI group. With a policy of elective single embryo transfer (eSET), twin rates after IVF-ICSI can be reduced to <5% and triplets to <1%. CONCLUSIONS: After OS, more triplets are found and the outcome of MP is worse. MP is known to be associated with morbidity, mortality, and economic and social risks. To counteract these complications (1.) better training for physicians performing OS should be encouraged and (2.) the Swiss law on reproductive medicine needs to be changed, with the introduction of eSET policies. This would lead to a dramatic decrease in neonatal and maternal morbidity/mortality as well as significant cost reductions for the Swiss healthcare system.